Do you read my signal? An attempt at the application of clear terminology in recording archaeological knitwork - Gilbert, Ruth (Archaeological Textiles Review, 2018)
The lack of a conventional approach to the analysis of knitted fabrics has led to limited information being available for the study of early knitting. This paper discusses some reports of finds of knitwork and applies a newly developed terminology and a proposed protocol for reporting archaeological and historical knitted textiles to four previously published artefacts to demonstrate their clarity in use. It points out the pitfalls of assuming how items were knitted without appropriate evidence. It also proposes that some characteristics of knitted fabric such as gauge and yarn diameter are essential for the comprehensive understanding and comparability of early evidence for knitting as a technique.